Islamization of Knowledge - Masudul Alam Choudhury (International Institute of Islamic Thought, 1992)
This well-written book comprehensively outlines the basic precepts on which a concept and a program of Islamization of knowledge must, according to the author, rest. In his attempt to outline these directions, the author first defines the concept of Islamization as " ... practising (i.e., discovering, compiling, piecing together, communicating and publishing) intellectual activity based on the Islamic concept of the universe" (p. 5). He further states that "'Islamization' covers everything within the realm of the true belief in the existence of Allah (SWT)" (p. 5). This definition is enhanced by Khalil's unequivocal reference to the Shari'ah and fiqh, the derivative of the Qur'an and the Sunnah, as being the principal background for the Islamization process. Another important aspect of Islamization, according to the author, is the absence of dualism in this framework. He says that in the quest for establishing the Islamic dimensions of belief in the diversity of human acquisitions, all "that might lead to dualism between the Divine orientation and its absolute knowledge and the conflicting relativism of human efforts" (p. 6) must be avoided. The author correctly points out that Islamization must be carried out on both the theoretical (normative) and the practical (positive) aspects of the sciences. It is here, however, that a series of questions arise and which, in turn, lead to a critical analysis that seemingly does not support the author's thesis on the modus operandi and worldview of Islamization. Internal inconsistencies within the arguments presented also lead to several difficulties. In my analysis of some of these problematic points, I will use the tawhidi precept that tenters the Islamization process. Islamizing the Natural and the Social Sciences Khalil says that the natutal and the social sciences are not amenable to the same degtee of Islamization. In his view, the social sciences will be Islamized before the natural sciences: "... sciences such as civil engineering, algebra, trigonometry or mathematics in general, as well as other disciplines like statistics, chemistry and possibly geology, may not be related to the process" (p. 7) ...